THE FLOWER YIELD OF MARIGOLD CALENDULA OFFICINALIS PLANT AND THE CONTENT OF CAROTENOIDS AND TOTAL PHENOLICS UNDER THE INFLUENCE OF SPRAYING WITH MORINGA LEAF EXTRACT AND YEAST AND ADDITION OF HUMIC ACID: THE FLOWER YIELD OF MARIGOLD CALENDULA OFFICINALIS PLANT AND THE CONTENT OF CAROTENOIDS AND TOTAL PHENOLICS UNDER THE INFLUENCE OF SPRAYING WITH MORINGA LEAF EXTRACT AND YEAST AND ADDITION OF HUMIC ACID (Iraqi Journal of Market Research and Consumer Protection, 2026)
A field experiment was carried out at College of Agricultural Engineering Sciences - University of Baghdad, during the fall seasons of 2021-2022 and 2022-2023. The aim of study the effect of foliar spraying with moringa extract and yeast, and the addition of humic acid was determi need, on the flower yield, carotenoids content, and total phenolics. A factorial experiment within a Randomized Complete Block Design (RCBD) with three replicates. Was implemeuted The study included three factors: foliar spraying with moringa leaf extract at concentrations of 0%,4%, 6% and 8% (M0-M1-M3-M2), yeast suspension at concentrations of 0 g L-1 , 5 g L-1 and 10 g L-1 (Y0-Y1-Y2), and adding humic acid at concentrations of 0 ml L-1 and 5 ml L-1 (H0-H1). Additionally, a control treatment (M0Y0H0) was included. The results showed a significant superiority of the interaction treatment M3Y2H1 in flower number, flower diameter, fresh flower yield, dry flower yield, carotenoid content, and total phenolics. Specifically, it recorded 37.43 flower plant-1, 7.960 cm, 571.3 kg ha-1, 78.81 kg ha-1, 168.6 mg 100 g-1, and 156.7 mg 100 g-1 for the first season and 35.15 flower plant-1, 7.950 cm, 523.2 kg ha-1, 72.33 kg ha-1, 164.5 mg 100 g-1, and 155.1 mg 100 g-1 for the second season, respectively, compared to the control treatment.